A philosophical landscape of the great problemns of the meta-ethics - Guevara Arroyo, Alejandro (2019)
This paper presents a philosophical panorama of the great problems and answers of the meta-ethics with the purpose that it is useful for those who want to immerse themselves in these complicated matters of contemporary philosophy. It means that its goal is informative and introductory to the study of the meta-ethics.